The burden of unhelmeted motorcycle injury: A nationwide scoring-based analysis of helmet safety legislation. Issue 3 (March 2023) - Ganga, Arjun; Kim, Eric J.; Tang, Oliver Y.; Feler, Joshua R.; Sastry, Rahul A.; Anderson, Matthew N.; Keith, Sharonda E.; Fridley, Jared S.; Gokaslan, Ziya L.; Cielo, Deus J.; Toms, Steven A.; Sullivan, Patricia Zadnik
Highlights: The stringency of motorcycle helmet safety legislation varies widely across the US. States with more stringent laws had significantly lower unhelmeted fatalities per 100, 000 people and 100, 000 motorcycles. Exemptions to helmet wearing for certain riders and motorcycle-like vehicles significantly predicted higher fatalities. Abstract: Introduction: Motorcycle collisions comprise a large portion of motor vehicle injuries and fatalities with over 80, 000 injuries and 5, 500 fatalities per year in the United States. Unhelmeted riders have poor medical outcomes and generate billions in costs. Despite helmet use having been shown to lower the risk of neurological injury and death, helmet compliance is not universal, and legislation concerning helmet use also varies widely across the United States. Methods: In this study, we systematically reviewed helmet-related statutes from all US jurisdictions. We evaluated the stringency of these statutes using a legislative scoring system termed the Helmet Safety Score (HSS) ranging from 0–7 points, with higher scores denoting more stringent statutes. Regression modeling was used to predict unhelmeted mortality using our safety scores. Results: The mean score across all jurisdictions was 4.73. We found jurisdictions with higher HSS's generally had lower percentages of unhelmeted fatalities in terms of total fatalities as well as per 100, 000 people and 100, 000 registered motorcycles. In contrast, some lower-scoring jurisdictions had over 100 times more unhelmeted fatalities than higher-scoring jurisdictions. Our HSS significantly predicted unhelmeted motorcycle fatalities per 100, 000 people (β = -0.228 per 1-point increase, 95% CI: -0.288 to -0.169, p < .0001) and per 100, 000 registered motorcycles (β = -6.17 per 1-point increase, 95% CI: -8.37 to -3.98, p < .0001) in each state. Aspects of our score concerning helmet exemptions for riders and motorcycle-type vehicles independently predicted higher fatalities ( p < .0001). Higher safety scores predicted lower unhelmeted fatalities. Conclusion: Stringent helmet laws may be an effective mechanism for decreasing unhelmeted mortality. Therefore, universal helmet laws may be one such mechanism to decrease motorcycle-related neurological injury and fatality burden. In states with existing helmet laws, elimination of exemptions for certain riders and motorcycle-type vehicles may also decrease fatalities.